2008
DOI: 10.1261/rna.1085008
|View full text |Cite
|
Sign up to set email alerts
|

The PIWI proteins SMEDWI-2 and SMEDWI-3 are required for stem cell function and piRNA expression in planarians

Abstract: PIWI proteins are expressed in germ cells in a wide variety of metazoans, where they participate in the synthesis and function of a novel class of small RNAs called PIWI associated RNAs (piRNAs). One function of piRNAs is to preserve the integrity of the germline genome by silencing transposons, though they also participate in epigenetic and post-transcriptional gene regulation. In the planarian Schmidtea mediterranea, the PIWI proteins SMEDWI-1 and SMEDWI-2 are expressed in neoblasts and SMEDWI-2 is required … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

17
253
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 224 publications
(271 citation statements)
references
References 47 publications
17
253
1
Order By: Relevance
“…2 E-G, bar graphs). Intergenic piRNAs have very high expression in neoblasts (Ͼ10-fold higher than in untreated whole-body planarians) and low expression in irradiated planarians (4-fold lower than in untreated planarians), consistent with the idea that piRNAs may be up-regulated in neoblasts and their division progeny, i.e., where PIWI proteins are specifically expressed (10). In contrast, total miRNA contents appeared roughly constant over the 3 samples, although the abundances of individual miRNAs varied.…”
Section: Comprehensive and Quantitative Deep Sequencing Of Planarian supporting
confidence: 73%
See 4 more Smart Citations
“…2 E-G, bar graphs). Intergenic piRNAs have very high expression in neoblasts (Ͼ10-fold higher than in untreated whole-body planarians) and low expression in irradiated planarians (4-fold lower than in untreated planarians), consistent with the idea that piRNAs may be up-regulated in neoblasts and their division progeny, i.e., where PIWI proteins are specifically expressed (10). In contrast, total miRNA contents appeared roughly constant over the 3 samples, although the abundances of individual miRNAs varied.…”
Section: Comprehensive and Quantitative Deep Sequencing Of Planarian supporting
confidence: 73%
“…Furthermore, our data contain the lowly expressed ''star'' miRNAs for 62 of the 63 miRNA genes. Another recent study reported Ϸ4,800 planarian piRNAs deep-sequenced from whole-body samples of planarians (10). We found 38% of these piRNAs in our data.…”
Section: Comprehensive and Quantitative Deep Sequencing Of Planarian supporting
confidence: 68%
See 3 more Smart Citations